Housing market dynamics in rural and regional Australia - Rowley, Steven (University of South Australia, 2012)
Rural and regional housing markets experience many of the same demand and supply drivers as their urban counterparts. However, there are many factors unique to rural and regional centres, both geographical and institutional, which have a significant impact on housing market dynamics. Many of these towns are ill equipped to deal with the rapid pace of change within their housing markets; from population growth stemming from mining activities or sea/tree change movements for example. The result is rapidly declining affordability leading to a range of social issues. But local government is often powerless to respond because it lacks the capacity and knowledge to deliver an appropriate supply response. Staffing and skill issues exist on the planning side but additionally, many towns missed out on government stimulus schemes to boost social housing supply, or deliver NRAS units, because they were unable to devote the time, or lacked the expertise, to complete the many complex application processes. Based on research funded by the Australian Housing and Urban Research Institute (final report no. 165), this paper details some specific examples where housing policy has failed towns and cities in rural and regional Australia. It discusses the decline of affordability, particularly in the private rental market, and recommends how policy could be better focused on delivering housing solutions within regional Australia. The paper concentrates on the case studies of Chinchilla and Townsville to illustrate housing market outcomes in rural and regional Australia.